1964
DOI: 10.1063/1.1724955
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study of Rotational Barriers and Conformational Preferences. I. Cyclohexyl Fluoride

Abstract: The equatorial:axial ratio and rate of conformational isomerization of cyclohexyl fluoride has been measured by observation of the 19F resonance as a function of temperature (—87.6° to +29.5°) for a 25 vol.% solution in CCl3F. Rate information is readily obtained over a wide temperature range, since the equatorial and axial fluorines differ in chemical shift by 20.5 ppm; the equatorial and axial α protons differ in chemical shift by only 0.46 ppm. Interpretation of the spectra in terms of isomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1967
1967
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Jensen and co-workers (10) have shown that this phenomenon is in fact general. Bovey et al (4) noted that the conformer ratio of cyclohexyl fluoride as determined by l H chemical shifts differed from the value obtained from area measurements. This discrepancy is now explained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jensen and co-workers (10) have shown that this phenomenon is in fact general. Bovey et al (4) noted that the conformer ratio of cyclohexyl fluoride as determined by l H chemical shifts differed from the value obtained from area measurements. This discrepancy is now explained.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Gutowsky-Holm equation (11) Using the value AGO = 0.650 kcal/mol, values of P D were calculated for each of the experimental spectra, and then the residence time T (= T) picked which most closely fitted the experimental peak width (4). The data are shown in Table 4.…”
Section: Rate Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation energies, AGfA+, and AG'E+A, were calculated from the coalescence temperature (T,) for the carbon 6 signal using two different methods developed for unequal proportions of conformers (44,45). Both methods gave practically the same values of activation energies, the largest difference observed being 0.2 kcal mol-I.…”
Section: -Acetoxytetrahydropyran (3)mentioning
confidence: 99%
“…The transition state for this process is thought to involve a half-chair structure with boat and twist-boat forms existing as intermediates along the reaction path ( Fig. 1) (3,(8)(9)(10)(11)(12). Typical barriers for ring inversion are 40-45 kJ mol-' while the energy differences between the equatorial and axial conformers are generally 0-4 kJ mol-' (3,7,8,13).…”
mentioning
confidence: 99%